MULTIVARIATE ANALYSIS ON PHENOTYPIC TRAITS OF BODY MEASUREMENT IN SWAMP BUFFALO ( Bubalus bubalis) - S. Johari; E. Kurnianto; S. Sutopo; W.A. Hamayanti (Diponegoro University, 2009)
The objective of this research was to study the relationship between body measurement and bodyweight and closeness among swamp buffalo at three populations in Central Java. The 110 heads ofswamp buffalo measured were from 29 heads of Pati district, 56 heads of Kudus district, and 25 heads ofSemarang city. Age of buffaloes used was 1-5 years old. The quantitative traits measured were bodyweight ( BW), body length (BL), shoulder height (SH), pelvic height (PH), chest depth (CD), chestcircumference (CC), chest width (CW), Pelvic width (PW), and waist width (WW). The data wasanalyzed by using multivariate procedure of SAS ver 6. The results showed that best equation toestimate BW for male buffalo was Y= - 601,8 + 2,3 BL + 3,4 CD + 2,4 CC, while that for female was Y= - 644,5 + 2,8 BL + 1,6 CD + 2,9 CC. Swamp buffalo in Semarang-Pati showed the closer relationshipscompared to the Pati-Kudus Districts and to Kudus District-Semarang City.